2007
DOI: 10.1556/abiol.58.2007.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Modification of antiallodynic and antinociceptive effects of morphine by peripheral and central action of fluoxetine in a neuropathic mice model

Abstract: We have previously reported that serotonin concentration was reduced in the brain of mice with neuropathic pain and that it may be related to reduction of morphine analgesic effects. To further prove this pharmacological action, we applied fluoxetine, a selective serotonin reuptake inhibitor, to determine whether it suppressed neuropathic pain and examined how its different administration routes would affect antinociceptive and antiallodynic effects of morphine in diabetic (DM) and sciatic nerve ligation (SL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Our results are consistent with a previous finding where the selective serotonin reuptake inhibitor (SSRI), fluoxetine, enhanced antinociceptive and antiallodynic effects of morphine in diabetic and sciatic-nerve-ligated mice [24]. Other reports also revealed that acute co-administration of serotonin and noradrenaline reuptake inhibitors (milnacipram and venlafaxine) and a tricyclic antidepressant (doxepin) with tramadol potentiated the antihyperalgesic effect of tramadol in the CCI model of neuropathic pain [17,26,28].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with a previous finding where the selective serotonin reuptake inhibitor (SSRI), fluoxetine, enhanced antinociceptive and antiallodynic effects of morphine in diabetic and sciatic-nerve-ligated mice [24]. Other reports also revealed that acute co-administration of serotonin and noradrenaline reuptake inhibitors (milnacipram and venlafaxine) and a tricyclic antidepressant (doxepin) with tramadol potentiated the antihyperalgesic effect of tramadol in the CCI model of neuropathic pain [17,26,28].…”
supporting
confidence: 93%
“…Mechanical hyperalgesia, observed after three weeks of diabetes, showed a reduced sensitivity to morphine-induced antinociception. This is consistent with numerous earlier reports of a significant reduction in the antinociceptive potency of morphine that was associated with hyperglycemic state in diabetes [4,5,24]. Alteration in the µ-opioid receptor function, an increase in the levels of interleukin-1b, and accumulation of morphine-3-glucuronide were reported in diabetic rats [9].…”
supporting
confidence: 92%
“…(5 mg/kg, ip) and MRF (5 mg/kg, sc) was inhibited by ketanserin and NLX in sciatic nerve ligation mice [10]. Our results suggested that both serotonin and noradrenaline mechanisms play a significant role in pain modulation after acute administration of MRF with VFX in STZ-induced neuropathic pain model.…”
Section: Tablementioning
confidence: 56%
“…Sounvoravong et al [10] revealed that ketanserine, a serotonin 2A receptor antagonist, and NLX blocked the combined antinociceptive effect of fluoxetine, a selective serotonin reuptake inhibitor, and MRF in neuropathic pain model.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the effects of fluoxetine are completely blunted in 5-HT depleted animals [227,233] suggesting that SSRIs-induced antinociception involves serotonergic pathways. In addition, fluoxetine but also fluvoxamine, paroxetine and sertraline significantly potentiated the analgesic effect of morphine [234-239] (Table 3). Although these effects were blocked by naloxone, fluoxetine did not alter the binding of [ 3 H]-naloxone demonstrating the lack of affinity of this SSRI for opioid receptors [239].…”
Section: Monoamines Reuptake Inhibitors and Pain Preclinical Outcomesmentioning
confidence: 99%